You Are What You Sing: Folksong tone pattern feature correlation to geographical distance with Gabor filter and OLS linear regression - Jason Kuanca (Universitas Multimedia Nusantara, 2020)
Cultural diffusion occurs. This is evidenced by the existence of cultural heritage artifacts. There are many types of artifacts, tangible or intangible. Folksongs are one of the intangible cultural artifacts. Songs have tone, tone patterns are a unique feature of a song. Regional province songs are the identity of each region, because songs are images of the culture of an area. This study uses folk songs from each province in Indonesia which are extracted features by applying Gabor filters and then differences in output and geographical distance are put into linear regression. The results show that the tone pattern feature have a correlation relationship with the distance between regions throughout Indonesia. When observing the scope per large island, there is also correlation between the number of tone patterns with the distance of province. However, this has less confidence result for Sumatra island.